Transcriptome Dynamics in Triticum aestivum Genotypes Associated with Resistance against the Wheat Dwarf Virus - Sharaf, Abdoallah; Nuc, Przemysław; Ripl, Jan; Alquicer, Glenda; Ibrahim, Emad; Wang, Xifeng; Maruthi, Midatharahally N; Kundu, Jiban Kumar (Viruses, 2023)
Wheat dwarf virus (WDV) is one of the most important pathogens of cereal crops worldwide. To understand the molecular mechanism of resistance, here we investigated the comparative transcriptome of wheat genotypes with different levels of resistance (Svitava and Fengyou 3) and susceptibility (Akteur) to WDV. We found a significantly higher number of differentially expressed transcripts (DETs) in the susceptible genotype than in the resistant one (e.g., Svitava). The number of downregulated transcripts was also higher in the susceptible genotype than in the resistant one (Svitava) and the opposite was true for the upregulated transcripts. Further functional analysis of gene ontology (GO) enrichment identified a total of 114 GO terms for the DETs. Of these, 64 biological processes, 28 cellular components and 22 molecular function GO terms were significantly enriched. A few of these genes appear to have a specific expression pattern related to resistance or susceptibility to WDV infection. Validation of the expression pattern by RT-qPCR showed that glycosyltransferase was significantly downregulated in the susceptible genotype compared to the resistant genotypes after WDV infection, while CYCLIN-T1-3, a regulator of CDK kinases (cyclin-dependent kinase), was upregulated. On the other hand, the expression pattern of the transcription factor (TF) MYB (TraesCS4B02G174600.2; myeloblastosis domain of transcription factor) was downregulated by WDV infection in the resistant genotypes compared to the susceptible genotype, while a large number of TFs belonging to 54 TF families were differentially expressed due to WDV infection. In addition, two transcripts (TraesCS7A02G341400.1 and TraesCS3B02G239900.1) were upregulated with uncharacterised proteins involved in transport and regulation of cell growth, respectively. Altogether, our findings showed a clear gene expression profile associated with resistance or susceptibility of wheat to WDV. In future studies, we will explore the regulatory network within the same experiment context. This knowledge will broaden not only the future for the development of virus-resistant wheat genotypes but also the future of genetic improvement of cereals for resilience and WDV-resistance breeding.
Keywords: resistance; Triticum; nemoci rostlin; Genotype; WDV; lidé; genotyp; šlechtění rostlin; virus; RNA-seq; Geminiviridae; wheat; transcriptome; Plant Diseases; genotype; transkriptom; pšenice; Plant Breeding; Transcriptome; Humans